2009
DOI: 10.1016/j.pbb.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and antinociception induced by a new pyrazolo[3,4-b]pyrrolo[3,4-d]pyridine derivative (LASSBio-873) is modulated by activation of muscarinic receptors

Abstract: New substances designed for the treatment of anxiety have previously been synthesized, which resulted in the identification of four new pyrazolo[3,4-b]pyrrolo[3,4-d]pyridine derivatives structurally designed by using zolpidem as lead compound. Among them, LASSBio-873 was the most potent to produce analgesic, sedative and hypnotic effects. Thus, we investigated the possible mechanisms involved in LASSBio-873-induced sedation, as well as its effects on different models of inflammatory pain. LASSBio-873 (4 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…In addition, our study provides evidence that the analgesic effect of LASSBio‐873 seems to be mediated through M 2 receptors, reinforcing the recent findings of Mendes et al . in mice . Although a previous study provided evidence for a sedative effect of LASSBio‐873, no effect on locomotor behaviour was observed after oral administration of LASSBio‐873.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, our study provides evidence that the analgesic effect of LASSBio‐873 seems to be mediated through M 2 receptors, reinforcing the recent findings of Mendes et al . in mice . Although a previous study provided evidence for a sedative effect of LASSBio‐873, no effect on locomotor behaviour was observed after oral administration of LASSBio‐873.…”
Section: Discussionmentioning
confidence: 78%
“…Some authors also demonstrated that activation of supraspinal M 1 receptors is very important for antinociceptive effects of cholinomimetic agents, such as xanomeline and McN‐A343, in neuropathic pain. In the present study, the role of M 1 receptor activation in the action of LASSBio‐873 was not investigated, but we have demonstrated previously the ability of LASSBio‐873 to activate this receptor subtype …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The reference drug Dzm was used at 2 mg/kg in the hole-board (Rao et al, 1999), activity cage (Silva et al, 2011), PTZ-induced seizure (Silva et al, 2011) and Hxbinduced sleeping tests (Silva et al, 2010). Antagonist compounds, including Nlx at 5 mg/kg (Zapata-Sudo et al, 2010), Atr at 2 mg/kg (Mendes et al, 2009) and Flu at 2.5 (Venâncio et al, 2011) and 10 mg/kg (Silva et al, 2011), were administered intraperitoneally 15 min before administration of the extract.…”
Section: Methodsmentioning
confidence: 99%